Combinatorial Auctions for Selling Network Capacity - Petr Fiala (Communications - Scientific letters of the University of Zilina, 2006)
The network economy is a term for today’s global relationship among economic subjects characterized by massive connectivity. Today’s network systems provide the infrastructure and foundation for the functioning of societies and economies. They come in many forms and include physical networks such as transportation and logistical networks, communication networks, energy networks, as well as more abstract networks as economic, financial, social, and knowledge networks. The paper presents modeling of auctions in network economy. Auctions are important market mechanisms for the allocation of goods and services. Combinatorial auctions are those auctions in which bidders can place bids on combinations of items. Combinatorial auction is an appropriate instrument for selling network capacity. The winner determination problem in a combinatorial auction for selling network capacity is formulated. The model can be formulated as a multicommodity flow problem and efficient algorithms can be used.